Ulnar Collateral Ligament Repair with Internal Brace Augmentation: A Novel UCL Repair Technique in the Young Adolescent Athlete - Walters, Brian L. (Orthop J Sports Med, 2016)
OBJECTIVES: Objective: Our purpose is to describe a novel surgical technique for Ulnar Collateral Ligament repair in the young adolescent, and present the clinical results of a retrospective cohort of patients. We hypothesized that using an internal brace to augment the repair of the native ulnar collateral ligament would allow for a more aggressive physical therapy protocol and ultimately facilitate both an expeditious return to sport and a high level of patient satisfaction. METHODS: Methods: After obtaining IRB approval for this study, our institutional electronic database was utilized to identify all patients who had undergone our novel technique for UCL repair between the years 2013-2014. An orthopedic fellow conducted phone surveys and the KJOC questionnaire was administered. Primary outcome measures included KJOC scores at 6 and 12 months, time to initiation of a plyometrics regimen, an interval throwing program and return to sports. Secondary measures including patient satisfaction, level of competition achieved and percent return to normal were also collected. RESULTS: Results: Twenty-two patients (19 male/3 female, average age 17.8 years) underwent surgery between 2013-2014. All patients were high school level athletes at the time of injury and included nineteen baseball players (13 pitchers), two football players, a javelin thrower and a cheerleader. Injury patterns included seven proximal tears, one mid substance, thirteen distal and four avulsions. Nine patients underwent ulnar transposition at the time of surgery, one had undergone prior transposition and the remainder of the patient’s ulnar nerves were left in situ. At six and twelve months the average KJOC scores respectively were 88.3 and 93. Patients that underwent transposition had KJOC scores of 78.3 at six months and 97.5 at twelve while patients that were left in-situ scored 82 and 91. These differences were not significant. The average number of weeks until initiation of plyometrics was seven and an interval throwing program was initiated on average, by week eleven. The average time to throwing from the mound was twenty weeks and full return to sports was twenty-one. Twelve of the thirteen pitchers made it back to the same or next level and six of them did so by transitioning from another position back to pitcher. The remaining athletes in the cohort all returned to competition at their pre injury level. At six months all but one patient was “very” satisfied and at twelve months, all were satisfied. At six months, patients deemed themselves to be at 92% normal and at twelve months, 96%. CONCLUSION: Conclusion: Recently, there have been an increasing number of throwing athletes with injuries to the ulnar collateral ligament (UCL) and a seemingly exponential rise amongst adolescents. The argument for repair rather than reconstruction in younger athletes is supported by both the observation that ligaments in these patients are absent the chronic attritional damage and secondary pathologic joint changes so frequently observed in injuries amongst higher-level athletes and the results of several recent clinical studies where a reliable and rapid return to overhead sports in this patient subset has been achieved. The current study demonstrates that our novel technique of UCL repair with internal brace augmentation shows early promise for accelerated therapy and ultimately faster return to play in adolescent athletes.